El juego infantil y su influencia en el desarrollo del proceso de enseñanza de los niños y niñas de 3 a 4 años, del INFA Municipio de Pasaje de la modalidad Creciendo con Nuestros Hijos del sector 10 de Agosto y Ricajer de la parroquia Buena Vista del cantón Pasaje periodo lectivo 2012-2013. - Matamoros León, Paola Elizabeth (2013)
Children's play and its influence on the development of the teaching of children aged 3 to 4 years, the municipality of passage mode grow with our children the sector on August 10 and ricajer of Buenavista parish passage canton period academic 2012-2013, the study is important because it will allow to know the level of knowledge, the type of game and methodology used by family educators in the teaching process.